Prognostic Function of Thinking in Altered State of Consciousness - S S Korneyenkov (RUDN Journal of Psychology and Pedagogics, 2011)
The prognostic ability of the personality in the altered state of consciousness is considered in the article. It is shown that in the altered state of consciousness the mind has the ability to reflect the information about the future events. The method of entering an altered state of consciousness is described.